1997
DOI: 10.1097/00006123-199710000-00020
|View full text |Cite
|
Sign up to set email alerts
|

Innervation Pattern of Malformative Cortical Vessels in Sturge-Weber Disease: An Histochemical, Immunohistochemical, and Ultrastructural Study

Abstract: These results demonstrate that nerve supplying cortical vessels in SWD are arranged in a distribution pattern similar to the one observed in human normal cortical veins and suggest that these abnormal vessels are innervated only with noradrenergic sympathetic nerve fibers. This represents a clear difference from the pattern of innervation observed in both normal cortical arteries and veins, and is the consequence of the anatomic and functional dysangiogenic process characteristic of the affected cortical areas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(13 citation statements)
references
References 22 publications
0
13
0
Order By: Relevance
“…MRI studies of cerebral perfusion performed in small groups of SWS patients demonstrated mostly decreased perfusion in regions with meningeal enhancement [11, 12]; additional perfusion defects were seen in areas of deep venous abnormalities. Based on histological studies, the cortical blood flow reduction was speculated to be secondary to the venous stasis and hypertension due to malformed, cortical vessels as well as venous thrombosis [1, 2, 24, 25]. Nevertheless, a SPECT study found hyper perfused cortex in some infants with SWS even before their first seizures [7].…”
Section: Discussionmentioning
confidence: 99%
“…MRI studies of cerebral perfusion performed in small groups of SWS patients demonstrated mostly decreased perfusion in regions with meningeal enhancement [11, 12]; additional perfusion defects were seen in areas of deep venous abnormalities. Based on histological studies, the cortical blood flow reduction was speculated to be secondary to the venous stasis and hypertension due to malformed, cortical vessels as well as venous thrombosis [1, 2, 24, 25]. Nevertheless, a SPECT study found hyper perfused cortex in some infants with SWS even before their first seizures [7].…”
Section: Discussionmentioning
confidence: 99%
“…34 Port-wine birthmark blood vessels lack perivascular nerves, 35,36 and SWS cortical vessels are innervated only by noradrenergic sympathetic nerve fibers. 37 Increased endothelin-1 expression was found in SWS vascular malformations. 38 Together these studies suggest that there may be increased vasconstrictive tone in the SWS brain vascular malformation; however, it is not known whether these alterations are pathologic or compensatory.…”
Section: Pathogenesis Of Sturge-weber Syndrome and Neurologic Progresmentioning
confidence: 98%
“…19 The vasoactive responses to temperature changes or seizures are also abnormal. Ictal spect (blood flow studies) in patients with Sturge-Weber syndrome have shown that during a seizure, blood flow can decrease to ischemic levels.…”
Section: Pathophysiologymentioning
confidence: 99%